Influence of Visual Media and Interest in Learning on Student Learning Outcomes in Social Sciences Subjects at SMP Negeri 1 Bunta - Palwati, Triana Juli; Puswiartika, Dhevy; Misnah, Misnah (PT. Riset Press International, 2024)
Education is one of the keys to nation development. Education must be carried out as fully as possible to achieve the expected goals. Formulation of the problem in the research. What is the description of visual media in social studies subjects at SMP Negeri 1 Bunta? Negeri 1 Bunta. The aim of the research is to determine the influence of visual media and interest in learning on student learning outcomes in social studies subjects at SMP Negeri 1 Bunta. This research method uses a survey method with a quantitative descriptive research type. The types of data and data sources used in the research are primary and secondary data . Primary sources are data sources that directly provide data to data collectors, and secondary sources are sources that do not directly provide data to data collectors, for example through other people or through documents. Furthermore, when viewed in terms of data collection methods or techniques, data collection techniques can be carried out by observation, interviews, documentation. The results of the research are that there is a significant influence between visual media and students' learning interest simultaneously on student learning outcomes.